FOOD INSECURITY IN ECUADORIAN HOMES DURING CONFINEMENT BY COVID-19 - Robayo, Carmen Viteri (2022)
Food security has been affected by the COVID-19 pandemic. The objective of the research was to evaluate access to sufficient, safe and nutritious food in the population of Ecuador. For this, the Latin American and Caribbean Scale was applied, validated with Cronbach's alpha statistic (? = 0.884), 478 online surveys were received and answered with prior informed consent. The data were analyzed from a descriptive and inferential statistics using the SPSS version 22 statistical package. As a result of the study, 77.3% of the households presented a moderate level of food insecurity, compared to 13.2% with severe insecurity. One of the main concerns in 73.5% of households was running out of food. The 39.9% of households maintain a little varied diet, without healthy and nutritious foods in it, 25.2% of adults and 11.9% of children under 18 years of age skip a meal during the day (breakfast, lunch, dinner). It is worrying that some member of the household, young or adult, (between 20 and 30%) eats less than what they consider they should eat, being hungry. Regarding gender, women are the ones with the greatest food insecurity, with no significant statistical difference; likewise, those who live in urban areas show greater insecurity compared to those who live in rural areas. Food security will be one of the challenges that local governments must face to safeguard the health of the population, for which new public policies will most likely be required.